(untitled) (Canadian Medical Education Journal, 2025)
Implication Statement The benefits of quiz-based games for education are well-recognized. Educators often struggle to find games that are suitably tailored to their students’ needs and easy to use. Gimkit, a new platform, allows instructors to create quiz games and host them in class. Based on student feedback and the literature, we developed a game mode for dental students called Save Our School (SOS) which is publicly available on the Gimkit Creative platform. Educators in the health professions can use this game to foster student engagement and perform formative assessments in their classes.